Importance of blood glucose self-monitoring in treatment of diabetes mellitus in the modern world - Elena V. Biryukova (LLC "MEDIAFORMAT", 2021)
Diabetes mellitus is a chronic disorder associated with microvasular and macrovascular complications, the prevention of which is an important challenge of modern medicine. Contemporary methods for diabetes management rely on the active involvement of the patient. Self-monitoring of blood glucose (SMBG) provides the basis for efficient antihyperglycemic therapy and prevention of hypoglycemia, as well as for the improvement of patient adherence to treatment. The importance of SMBG has further increased during the COVID-19 pandemic, since the adequate glycemic control can reduce the risk of COVID-19 infection and the disease severity in patients with DM. The recommended frequency of SMBG in patients with DM is discussed. A variety of glucose meters are available for measurement of blood glucose. Compliance with accuracy standards, simplicity and convenience for patients are the important criteria for selecting the glucose meter.